The Female FTSE Report 2008: A Decade of Delay - Sealy, Ruth; Vinnicombe, Susan; Singh, Val (Cranfield School of Management, 2008)
2008 marks our tenth index and report with a slight, incremental increase ofdirectorships held by women on the FTSE 100 corporate boards, bringing the totalnumber to 131. Ten years ago there were only 66 women on the FTSE 100 boards.The most meaningful increase has occurred in the 39 companies that now each havetwo or more women on their boards.